2021
DOI: 10.3389/fmed.2021.648899
|View full text |Cite
|
Sign up to set email alerts
|

Dental Education in the Time of COVID-19 Pandemic: Challenges and Recommendations

Abstract: Moving within the second wave of the coronavirus (COVID-19) pandemic, dental education delivery has been profoundly affected by this crisis, so has the structure, evaluation, and future of dental education. Both pre-clinical and clinical dental education have experienced challenges ranging from fully online educational content to limited dental training for senior dental students. This crisis appears to be a tipping point that produced confusion in dental teaching especially clinical sciences. Although medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…COVID-19 has affected the educational process at all levels. The majority of the educational institutions during the first and the second waves closed campuses and transitioned from physical attendance to virtual learning (Hassan and Amer, 2021). Early in this pandemic, many countries, including Egypt, began to implement precautionary measures, such as social distancing and lockdowns of educational institutions in order to control and mitigate the pandemic (Social Distancing, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 has affected the educational process at all levels. The majority of the educational institutions during the first and the second waves closed campuses and transitioned from physical attendance to virtual learning (Hassan and Amer, 2021). Early in this pandemic, many countries, including Egypt, began to implement precautionary measures, such as social distancing and lockdowns of educational institutions in order to control and mitigate the pandemic (Social Distancing, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dental institutions recognized the challenges this pandemic presented to dental students (Barabari and Moharamzadeh, 2020;Hung et al, 2021). Specifically, the pandemic affected clinical training for dental students, which could delay them from taking regional dental board exams or completing other graduation requirements (Hassan and Amer, 2021;Hung et al, 2021). In Egypt, the Ministry of Higher Education and Scientific Research authorized the replacement of ongoing classroom teaching with e-learning for both undergraduate and postgraduate education using various software and interactive online platforms (Hassan and Amer, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a stronger impact on dental education was imposed by the pandemic. This issue has been described as one of the major challenges for dental education during COVID-19 pandemic [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…9 For example, clinical training of dental students temporarily relied on case presentations, rather than experiential learning alongside practicing clinicians due to infection control precautions. 10 Another report found that 70% of medical students reported worsening mental health during the initial months of the pandemic. 11 Prospective cohort studies of health professional students initiated during the COVID-19 pandemic could provide much needed information about changes in the physical, mental, and social health of students during the pandemic and their occupational trajectory as they enter the health professional workforce.…”
Section: Introductionmentioning
confidence: 99%